Development of Segregated Recycle Waste System - Kwan, Loh Soo; Sanudin, Rahmat (Evolution in Electrical and Electronic Engineering, 2020)
Waste recycling issues have been a common topic in recent decades. A dramatic waste stockpile is a concern due to its bad impact on the environment. This project aims to design a recycle bin that could identify and differentiate recyclable waste, there are aluminium can and plastic, split them into the respective trash bin, detect the trash level and transfer the real-time data to an online cloud. A recycling system with four sub-systems, entry system, detection system, segregation system with IoT feature was successfully created in this study. The entry system works to activate the three other sub-systems once trash placed into the system. Results suggest that the detection system works as expected to identify, differentiate and segregate different type of waste. It is concluded that the segregated system works well for recycling waste and it is anticipated that it could contribute towards an improved waste management system.